STRATEGI PEMASARAN KOPI BIJI SALAK â€œKOBISAâ€ DI DESA PANGU KECAMATAN RA-TAHAN TIMUR KABUPATEN MINAHASA TENGGARA - Gabriella F. Ompi; Caroline B.D. Pakasi; Nortje M. Benu (COCOS, 2016)
ABSTRACTSoutheast Minahasa Regency, one of the areas in North Sulawesi is a region with a leading sectors namely agriculture sector. Subdistrict Ratahan East is one of the districts in Southeast Minahasa Regency is known as a regional fruit "bark" is specifically located in the village of Pangu. It turned out that the content of this KOBISA has health benefits for the body humans. Many strategies regarding marketing mix 4P made by CV. Culinary Saguer namely: Product, price, place, promotion.Key words: marketing strategy, coffee beans salak, marketing mix